(untitled) (Revista Electrónica REDINE, 2021)
University social actors have experienced challenges and challenges in a globalized world of cultural knowledge, where technology has been present in the different paradigmatic perspectives. The present reflection essay, of a documentary nature, from an interpretive paradigm, aims to show the importance of virtualization as a new culture where teachers and students significantly construct virtual learning, without leaving the traditional, but unifying them to achieve the teaching purposes and research, that transform the educational task in Higher Education, promoting an interactive paradigm of cooperation and learning.